Antifertility activity of Oroxylum indicum Vent. stem bark on female Wistar rats - Banani Das; Madhusmita Mahapatra
Plant based traditional medicines are being used by the diversified populations of North-East India (NE India) for numerous human ailments and birth control since ancient times. Different ethnic communities of the Indian state Tripura have been traditionally using fresh stem bark of Oroxylum indicum (L.) Vent. for birth control. Thus, the aim of this research was to justify pharmacologically the traditional use of Oroxylum indicum stem bark for birth control. The ex-vivo uterotonic potential of four different extracts viz., ethyl acetate (EAOI), acetone (ACOI), methanolic (MEOI) and aqueous (AEOI) extracts (10 (So(Bg/50 (So(BL) of O. indicum stem bark was carried out using uterine tissue and 4%, 16%, 53% and 89% uterine contraction, respectively was observed. Hence, 200 mg/kg/day dose of MEOI and AEOI were investigated on female rats for in-vivo abortifacient and anti-implantation activity and the level of different hormones released were estimated. In addition, acute-toxicity of the MEOI and AEOI were carried out on rats of either sex. The AEOI extract showed height potential for both aborticide (**p<0.01) and anti-implantation effect (**p<0.01) in compared to MEOI extract. It was noticed that there was a significant decline (**p<0.01) in gonadotropic releasing hormone (GnRH) level in anti-implantation model and major elevation (**p<0.01) in luteinizing hormone (LH) level of anti-implantation and abortifacient model in both standard and treatment group, where Ethinylestradiol (0.1 mg/kg/day, P.O.) used in standard group and the treatment group received AEOI. In acute toxicity studies, both the test samples of MEOI and AEOI have not exhibited any toxic effect up to 2000 mg/kg dose. Based on the pharmacological aspect, the present study justifies the traditional claim for O. indicum as an antifertility agent and identifies the potential of AEOI as an excellent and safe source of antifertility agents